2016
DOI: 10.12913/22998624/64021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curing Temperature in the Alkali-Activated Blast-Furnace Slag Paste and Their Structural Influence of Porosity

Abstract: Due to the environmental problem posed by the use of Portland cement as construction material, it becomes necessary the search for supplementary cementitious materials that mitigate the ecological damage caused by it. Because the chemical similarity and the high cementitious powers of the blast furnace slag, it is used in the generation of geopolymers in a cement total replacement. This research focused on the study of the influence of the curing conditions on the final properties of blast furnace slag establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In the case of AACMs, earlier research has shown a need for high temperature curing at 50 -80 0 C, such as steam or dry heat, for optimum geopolymerization reaction [2,11]. More recent work uses ambient temperature (20 ± 2 0 C), which is practical on construction site, for curing AACMs [12,13]. The optimum levels of relative humidity required for AACM curing are not established.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of AACMs, earlier research has shown a need for high temperature curing at 50 -80 0 C, such as steam or dry heat, for optimum geopolymerization reaction [2,11]. More recent work uses ambient temperature (20 ± 2 0 C), which is practical on construction site, for curing AACMs [12,13]. The optimum levels of relative humidity required for AACM curing are not established.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the properties of precursors and the composition of activators, curing conditions (e.g., curing temperatures, curing time, and curing humidity) have been also demonstrated to affect chloride resistance in AAMs due to the changes in the kinetics of the reaction. Furthermore, experimental evidence has suggested that the changes in the kinetics of the reaction have impacts on improving the development of microstructures [23,129,140]. Table 5 lists the curing conditions affecting the chloride resistance of AAMs.…”
Section: Curing Conditionsmentioning
confidence: 99%
“…More specifically, the high-temperature curing in AAMs contributes to decreasing chloride penetration as a result of the reduced average pore sizes and reduced porosity [108,140,142,143]. Additionally, it is also reported that curing under a higher temperature can accelerate the dissolution of precursors and influence the overall generation of reaction products [14,90,144].…”
Section: Curing Conditionsmentioning
confidence: 99%
“…Nevertheless, the history of alkali-activated cement is dated to the 1940s by Glukhovsky and then Krivenko [2,3]. Geopolymers (GP in the following text) are formed by alkaline activation of thermally treated aluminosilicate material like fly ash [4][5][6][7], furnace slag [8][9][10], kaolinite clay [11][12][13] etc. A reaction called geopolymerization creates polymeric Si-O-Al bonds in a three-dimensional network [14].…”
Section: Introductionmentioning
confidence: 99%
“…The negative charge of alumina tetrahedrons is balanced by the presence of alkali-metal ions, commonly Na + , K + or Ca + [14]. Several investigations considering the precursors' composition and curing conditions have been done [8,15,16].…”
Section: Introductionmentioning
confidence: 99%